On the phase space of free higher-spin theories and conformal transformations - Flores, Henrique [UNESP] (Elsevier B.V., 2017)
We write a first order action for higher-spin fields and construct a canonical map to Fronsdal theory. The first-order description is defined over complex field configurations and has conformal invariance. We show that it is possible to push forward these transformations to a set of symmetries in Fronsdal theory that satisfies the conformal algebra but is not given by standard conformal change of coordinates. (C) 2017 The Author. Published by Elsevier B.V.